2016
DOI: 10.1186/s40461-016-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotional states during learning situations and students’ self-regulation: process-oriented analysis of person-situation interactions in the vocational classroom

Abstract: IntroductionTheoretical and empirical aspects of interactions between person and situation have been discussed for decades in personality and social psychology in terms of the interactionist paradigm (e.g. Matthews et al. 2003), in educational psychology within the scope of aptitude-treatment interaction theory (e.g. Cronbach and Snow 1977;Yeh 2012), and in vocational education and training (VET) in terms of the process-oriented research approach, investigating antecedents and effects of successful teaching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Thus, from a methodological point of view, the application of cross-classified data structures and corresponding multilevel statistical models (e.g., Heck et al 2010) seems to be the method of choice. In that regard, cross-classification considers that multiple state measures are not only nested within persons, but that they also belong to observation units of the working context corresponding to the time of measurement (Goldstein 1994; Hill and Goldstein 1998; for applications see, for example, Kaerner and Koegler 2016;Kaerner et al 2017;Kaerner and Warwas 2018). Figure 5 illustrates a cross-classified data structure with person-related states (e.g., varying HR or RMSSD values, or stress experience) nested within persons/teachers (1…n; e.g., varying levels of psychological resilience or coping skills) working in a specific working context (1…k; e.g., different types of schools) and exposed to continuously changing context conditions (1…t; e.g., varying levels of work-related demands).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, from a methodological point of view, the application of cross-classified data structures and corresponding multilevel statistical models (e.g., Heck et al 2010) seems to be the method of choice. In that regard, cross-classification considers that multiple state measures are not only nested within persons, but that they also belong to observation units of the working context corresponding to the time of measurement (Goldstein 1994; Hill and Goldstein 1998; for applications see, for example, Kaerner and Koegler 2016;Kaerner et al 2017;Kaerner and Warwas 2018). Figure 5 illustrates a cross-classified data structure with person-related states (e.g., varying HR or RMSSD values, or stress experience) nested within persons/teachers (1…n; e.g., varying levels of psychological resilience or coping skills) working in a specific working context (1…k; e.g., different types of schools) and exposed to continuously changing context conditions (1…t; e.g., varying levels of work-related demands).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future studies should use video-based observations of what is going on in the classroom and use established coding systems such as the "Instrument to Identify Regulation Hindrances in Industrial Work" (RHIA) to identify regulation barriers and capacity-overtaxing factors in classroom teaching (Meder et al 2008). Combining information about "objective" situational context conditions with information on self-reports along with physiological measures (e.g., Kaerner and Koegler 2016;Kaerner et al 2017) seems to be fruitful and would give us better insights about teachers' stress in the classroom (for a good methodological example, see Donker et al 2018).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Taking into account that individuals' states (such as physiological reactivity to demanding situations) are affected not only by situational conditions but also by personal characteristics (cf. Kärner and Kögler 2016;Kärner et al 2017), the interaction effect found between vocational experience and goal elaboration provides evidence for person-situation interactions, also within narrowly defined vocational problem-solving situations.…”
Section: Stress-reducing Potentials Of Personal Characteristics (Rq2)mentioning
confidence: 93%
“…Lindberg 2003Lindberg , 2019, students' identity work (Åberg and Hedlin 2015), and more general pedagogical issues (cf. Khaled et al 2016;Kärner and Kögler 2016;Schaap, van der Schaaf, and de Bruijn 2017). Hämäläinen and Cattaneo (2015), for example, examine how emerging technology-enhanced learning settings in school settings in Finland and Switzerland mediate instructional activities when teacher and students interact.…”
Section: Previous Researchmentioning
confidence: 99%